ANALISIS KREATIVITAS MATEMATIS SISWA SMA MELALUI PROJECT BASED LEARNING TERINTEGRASI STEM PADA PEMBELAJARAN FISIKA ELASTISITAS DI KELAS XI MIPA 6 SMAN 2 JEMBER - Nuri Ade Iksani Devi; Albertus Djoko Lesmono; Heni Mulyo Widodo (JURNAL PEMBELAJARAN FISIKA, 2020)
This study examines STEM (Science, Technology, Engineering, and Mathematics) as one approach that is integrated with the project based learning model. This study aims to analyze the mathematical creativity of high school students through the integrated STEM project based learning model in learning physics material elasticity. The research method used was a pre-experimental design with the One Group Post-test Only Design which was carried out in class XI MIPA 6 of SMAN 2 Jember with 36 students consisting of 14 male students and 22 female students formed in 6 heterogeneous groups each - each group consisted of 6 people. Data collection was performed using the final test in the form of analysis of student worksheets and video analysis of student learning processes to measure students' mathematical creativity. Based on the results of the study, it was found that the application of STEM integrated project based learning affected the mathematical creativity of high school students in class XI MIPA 6 of SMAN 2 Jember.